2021
DOI: 10.5194/tc-15-4873-2021
|View full text |Cite
|
Sign up to set email alerts
|

Local-scale deposition of surface snow on the Greenland ice sheet

Abstract: Abstract. Ice cores from polar ice sheets and glaciers are an important climate archive. Snow layers, consecutively deposited and buried, contain climatic information from the time of their formation. However, particularly low-accumulation areas are characterised by temporally intermittent precipitation, which can be further redistributed after initial deposition, depending on the local surface features at different spatial scales. Therefore, the accumulation conditions at an ice core site influence the quanti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 73 publications
3
30
0
Order By: Relevance
“…Temperatures below -25 • C are characterised by the same slope defined by the model (-0.54 m 2 kg −1 day −1 ), but with a significantly higher intercept of 29 m s −1 day −1 compared to 14.7 m s −1 day −1 for temperatures above -25 The characterization of the SSA decays provide a basis to explore how snow metamorphism of surface snow plays a role for the alteration of isotopic composition of Greenland snow after deposition. A recent study at EastGRIP has shown the significant in-homogeneity in surface snow due to post-depositional reworking of the snow (Zuhr et al, 2021). The focus for this manuscript is to identify signal coherence between physical properties and isotopic composition of surface snow subject to during 2018 and 2019 seasons, while the signal is less clear during 2017 (Fig.…”
Section: Environmental Conditions During Ssa Decay Eventsmentioning
confidence: 99%
“…Temperatures below -25 • C are characterised by the same slope defined by the model (-0.54 m 2 kg −1 day −1 ), but with a significantly higher intercept of 29 m s −1 day −1 compared to 14.7 m s −1 day −1 for temperatures above -25 The characterization of the SSA decays provide a basis to explore how snow metamorphism of surface snow plays a role for the alteration of isotopic composition of Greenland snow after deposition. A recent study at EastGRIP has shown the significant in-homogeneity in surface snow due to post-depositional reworking of the snow (Zuhr et al, 2021). The focus for this manuscript is to identify signal coherence between physical properties and isotopic composition of surface snow subject to during 2018 and 2019 seasons, while the signal is less clear during 2017 (Fig.…”
Section: Environmental Conditions During Ssa Decay Eventsmentioning
confidence: 99%
“…For evaluating the importance of sublimation for the summer signal in the snowpack isotope record the comparison of the precipitation versus the sublimation signal both in terms of mass balance and preserved signal seems necessary. However, with no information about the precipitation's isotopic composition and mass (Zuhr et al., 2021 ), this comparison is infeasible. Instead, we calculate the observed change in snow isotopic composition during the observation periods and exclude days with snowfall or wind redistribution.…”
Section: Discussionmentioning
confidence: 99%
“…Besides uneven deposition through precipitation intermittency (Casado et al., 2020 ; Münch et al., 2021 ; Persson et al., 2011 ) and precipitation seasonality (Cuffey & Steig, 1998 ; Zheng et al., 2018 ), wind redistribution (Zuhr et al., 2021 ) and mixing with drifting snow (Stenni et al., 2016 ), post‐depositional processes are suggested to alter the isotopic composition of the snow. Specifically, vapor‐snow exchange processes occur continuously at the surface through turbulent humidity fluxes (Wahl et al., 2021 ) which are defined by local climate and below the surface during snow metamorphism.…”
Section: Introductionmentioning
confidence: 99%
“…The ice core SMB record can also be strongly modified by post-depositional reworking of the surface by winds that can erode away snow in one location and redeposit it several kilometers away or remove it completely through wind-driven sublimation (King and others, 2004; Lenaerts and others, 2019; Agosta and others, 2019). SMB can be highly variable, even over the distance of a few meters (Gautier and others, 2016; Kausch and others, 2020; Münch and others, 2021), and post-depositional reworking can further modify this spatial SMB variability (Zuhr and others, 2021). With a surface area of cm, ice cores therefore have the potential to capture a local and noisy record of past SMB conditions.…”
Section: Introductionmentioning
confidence: 99%